(3GdBdGJ GdYLjHI GdQUOjIs - (3CHh GdaJM YHO GdQMef GdefUhQ GdNGRfj,J (B550 (3g` s
(3ChdgG (B:s
(3aGdbSe GdChd(B: (3ef GdChdi jTJed Ydi UfYI GdBdI hcjajI ESJYeGdgG hUhQJgG Ydi gjFJjf , EMOGgeG ceG PcQg HWdjehS ai GdeLSWi dESJNQGL EQJaGY GdbeQ hGNJdGa efXQg HgG s
(3BNQgG (B:s
(3djcf CQWhd GdefGQI , hg` OQ NTHI bGFeI Ydi GdCQV ai GdfXQ GdChd , hM O bGFeI GdfGXQ , h M g` GdbOQ GdChd ai YOO GdJCNQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG CTcGd hQShe gfOSjIs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3ChQGbgG eVWQHI GdJQJjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B305 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B124s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs